Learning and using SAS in agricultural research - A. Halim, Ridzwan; Ahmad, Siti Hajar (1987)
SAS statistical package is currently integrated into courses in statistics and research methods in many US Universities. This paper describes the authors' experience in learning SAS as part of their course work in statistics. The authors' dissertation is used as an example of the application of SAS in agricultural research. At Universiti Pertanian Malaysia (UPM), SAS has only been recently available on PC's. Plans are underway to incorporate SAS in the teaching of statistical courses at UPM.